A validated lateral response model for mass timber frames with knee-braces. (15th July 2021) - Cao, Jixing; Xiong, Haibei; Ghahari, S. Farid; Taciroglu, Ertugrul
Highlights: Failure modes of Mass-Timber Frames with Knee Braces (MTF-KB) are investigated under cyclic loading. Particle Filtering is adopted to estimate the parameters of a hysteretic model from test data. Seismic performance of a variety of MTF-KB configurations are evaluated. An energy-based damage index (0 to 1) is devised that relates visual observations to damage. Abstract: Efforts to increase the use of renewable materials in construction are pushing the use of timber frames into new boundaries—for example, as lateral load-resisting systems in medium to high-rise buildings. This drive brings forth higher performance requirements for timber structures against hazards such as fires and earthquakes. The present study focuses on the development and parameter calibration of a cyclic lateral response model for mass timber frames with knee-braces (MTF-KBs) through a full-scale test. The model primarily comprises plastic hinges, which represent the hysteretic behavior of the MTF-KB specimen. The model parameters are estimated from test data using a Particle Filter (PF) method, which yields the optimal parameters together with their uncertainties. The calibrated model is then used in parametric studies to examine their lateral response, including stiffness and strength degradation, and damage evolution. The performance of MTK-FB in various single- and multi-story structural configurations is also investigated based on this calibrated model, and a novel energy-based damage index is devised that maps visual observations to various thresholds of damage. The proposed MTK-FB model can be readily recalibrated to new/other experimental data. Moreover, the PF-based model updating method presented in this study can be applied to any hysteretic force-displacement data that exhibit complex behavior such as cycle degradation, inelastic deformations, and pinching. The availability of model parameter uncertainties is a useful feature for performance-based seismic assessment studies.